2019
DOI: 10.35814/mindset.v10i01.735
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Parenting Style and Children's Emotional Development among Indonesian Population

Abstract: The current research investigated the relationship between parenting style and emotional regulation among children in Indonesian population. A total of 126 parents of children aged between 3 and 6 years old participated in this study. The Parenting Styles and Dimensions Questionnaire Short Version (Robinson, Mandleco, Olsen, & Hart, 2001) was used to measure parents’ parenting style, and the Emotion Regulation Checklist (Shields & Cicchetti, 1997) was used to measure parents’ perceptions of children’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
1
7
0
8
Order By: Relevance
“…Sikap dan perilaku yang diterapkan oleh orang tua siswa kelas V SD Dana Punia Singaraja cenderung memberikan kebebasan namun tetap memperhatikan, membatasi, serta selalu mendampingi anak. Hal ini sejalan dengan teori pola asuh dari Baumrind (dalam Boediman & Desnawati, 2019;Sumargi et al, 2020) yang menyatakan bahwa pola asuh demokratis adalah pola asuh yang memberikan keseimbangan antara menempatkan batasan dan kontrol yang realistis dengan dukungan dan kehangatan. Pendidikan demokratis merupakan proses dalam mendidik dengan memberikan kesempatan yang sama kepada seluruh anak untuk mendapatkan input yang sesuai dengan kemampuannya (Nur & Sudarsono, 2018;Rohmania et al, 2021).…”
Section: ) Menekankan Kerja Sama Dalam Mencapai Tujuanunclassified
See 1 more Smart Citation
“…Sikap dan perilaku yang diterapkan oleh orang tua siswa kelas V SD Dana Punia Singaraja cenderung memberikan kebebasan namun tetap memperhatikan, membatasi, serta selalu mendampingi anak. Hal ini sejalan dengan teori pola asuh dari Baumrind (dalam Boediman & Desnawati, 2019;Sumargi et al, 2020) yang menyatakan bahwa pola asuh demokratis adalah pola asuh yang memberikan keseimbangan antara menempatkan batasan dan kontrol yang realistis dengan dukungan dan kehangatan. Pendidikan demokratis merupakan proses dalam mendidik dengan memberikan kesempatan yang sama kepada seluruh anak untuk mendapatkan input yang sesuai dengan kemampuannya (Nur & Sudarsono, 2018;Rohmania et al, 2021).…”
Section: ) Menekankan Kerja Sama Dalam Mencapai Tujuanunclassified
“…Dalam prosesnya orang tua lebih sering memberikan pengertian, penjelasan, dan penalaran untuk membantu anak mendapatkan pemahaman atas perilaku yang diharapkan. (Boediman & Desnawati, 2019;Khosiah et al, 2021).…”
Section: ) Menekankan Kerja Sama Dalam Mencapai Tujuanunclassified
“…A study conducted by Sunarty and Dirawan [23] found that the type of parenting style affects children's independence, especially related to learning activities. Furthermore, Boediman and Desnawati [24] who conducted a study on 126 parents of children aged 3 and 6 years revealed that there is a positive relationship between parenting style and the development of children's emotional regulation. Specifically, Leijten, et al [25] examined the impact of parenting in the form of verbal reprimands.…”
Section: Types Of Parenting Patterns and Characteristics Of Childrenmentioning
confidence: 99%
“…Most of them apply parenting styles that do not show the characteristics of authoritarian parenting. Authoritarian parenting has characteristics such as using rigid, firm rules, likes to punish, lack of affection, lack of sympathy and so on [22] [23] [24]. On the other hand, the informants always try to give love and attention to children in various forms.…”
Section: Authoritarian Parentingmentioning
confidence: 99%
“…Parenting style also affected children's socio-emotional development. Children whose parents implemented authoritative parenting style had better socio-emotional condition compared to children whose parents implemented authoritarian or permissive parenting style [8]- [10]. This better socio-emotional condition can be seen through the level of problem behavior in children.…”
Section: Introductionmentioning
confidence: 99%